The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1971
DOI: 10.1063/1.1660773
|View full text |Cite
|
Sign up to set email alerts
|

Alloying Behavior of Au and Au–Ge on GaAs

Abstract: Although Au–Ge has often been used in making Ohmic contacts to GaAs, the alloying behavior of this system has not been well characterized and understood. In this paper the behavior of Au and Au–Ge layers on GaAs was investigated as a function of processing temperature (400–600°C) and time by backscattering and channeling-effect measurements with 2-MeV 4He ions. Scanning electron microscopy and current-voltage evaluations were also made. Similarities are found in both systems: There is a deeply penetrating comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(15 citation statements)
references
References 8 publications
3
12
0
Order By: Relevance
“…The ohmic contacts are deposited and heat treated. The present metallurgy utilizes gold-germanium alloys because it has been found that lower resistance contacts are formed with about twenty atomic percent germanium in the gold (14,19). Although there is no direct evidence, it is believed that the germanium becomes incorporated in the GaAs lattice during heat-treatment and forms ahigh n-type dopant concentration immediately adjacent to the metallic contact interface.…”
Section: Tunnel Schottky Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The ohmic contacts are deposited and heat treated. The present metallurgy utilizes gold-germanium alloys because it has been found that lower resistance contacts are formed with about twenty atomic percent germanium in the gold (14,19). Although there is no direct evidence, it is believed that the germanium becomes incorporated in the GaAs lattice during heat-treatment and forms ahigh n-type dopant concentration immediately adjacent to the metallic contact interface.…”
Section: Tunnel Schottky Barriersmentioning
confidence: 99%
“…One method of making gold ohmic contacts to an n-type semiconductor is therefore to heat the sample. For example in studies (19) of ohmic contacts to gallium arsenide, GaAs, which is a III-V compound semiconductor used for high speed devices, heat treatment of gold coated GaAs at temperatures of 400 to 600°C produced a deeply penetrating component of gold in the semiconductor. A disordered region was found near the surface with the amount of disorder increasing with process time and temperature.…”
Section: The Importance Of Gold Schottky Barriersmentioning
confidence: 99%
“…Some arise from the non-uniform way in which the alloying occurs (19). However, the most serious problems arise from the redistribution of the Au, Ge, and Ga during the alloying (21,(24)(25)(26).…”
Section: Purpose and Motivation For This Researchmentioning
confidence: 99%
“…The usual technique utilizes the alloying of a Au-Ge contact mixture into the GaAs surface (18)(19)(20)(21)(22). The Ge is believed to move into the GaAs surface thereby creating a highly doped region which forms a thin space charge layer through which electrons can tunnel.…”
Section: Purpose and Motivation For This Researchmentioning
confidence: 99%
See 1 more Smart Citation